Proposed Model to Minimize Machining Time by Chip Removal Under Structural Constraint Taking into Consideration Machine Power, Surface Finish, and Cutting Speed by Using Sorting Algorithms - Abraham Manilla-García; Néstor F. Guerrero-Rodriguez; Ivan Rivas-Cambero (Applied Sciences, 2025)
This article proposes a model to estimate the optimal cutting speed and depth of cut used in the machining process by chip removal during the turning operation, considering the structural integrity of the workpiece to be machined. The structural integrity model is proposed considering the rounding of the cutting tool nose as a measure of roughness requested in the workpiece, the electrical power capacity delivered by the machine tool motor as a load-limiting factor for the process, the geometry of the desired workpiece, and the physical machining parameters given by cutting tool manufacturers. Based on these criteria, an estimation algorithm is proposed that integrates these parameters and executes the search for the optimal cutting depth and cutting speed, meeting the structural integrity criterion in accordance with the minimum machining time criterion in the turning process, establishing a balance between process reliability and minimization of machining time. The proposed model is innovative since it presents a new methodology to determine the depth of cut and calculate the machining speed under the criterion of preserving the structural integrity of the piece to be machined to the maximum. This means that the depth of cut and spindle speed estimated under the proposed methodology guarantee that during the machining process, the workpiece will not suffer structural damage from the cutting forces involved in the machining process, minimizing the effects of loading in areas of stress concentration, thereby contributing to highlighting and involving the concept of process reliability. This model provides a new theoretical method for technologists involved in the calculation of the machining process, offering them a theoretical basis for their proposals for depth of cut and cutting speed.